Analisa Perilaku Pasar Terhadap Purchase Intention Of Premium Sportswear ( Footwear & Apparel ) Brand â€œ Xâ€ Melalui Online Shopping Di Pulau Jawa, Indonesia - Kurniawan, Ellihu Yona; Bayu Dirgantara, I Made (JURNAL ILMIAH EDUNOMIKA, 2023)
This research aims to analyze market behavior regarding purchase intention of premium Sportswear (Footwear & Apparel) brand "X" through online shopping on the island of Java, Indonesia. The type of research used in this research is quantitative research. The source of the data obtained comes from a sample of respondents who filled out the questionnaire. The population of Indonesian society is the object. Indonesia itself is an archipelagic country which is divided into 5 large islands, namely Sumatra, Kalimantan, Java, Bali & Nusa Tenggara, Sulawesi, and Maluku & Papua. To provide an adequate level of confidence in this research, a sample size of 150 respondents was targeted. The statistical data analysis tool used for this research model is Structural Equation Modeling (SEM). The research results show that innovation has a positive effect on business performance. This means that the better the innovation implemented, the main aim of this research is to analyze what factors can influence the Purchase Intention of consumers/potential consumers in the context of online shopping for brand X premium sports products. Several variables have a research gap when determining the Purchase Intention of consumers/potential consumers. Keywords : market behavior, purchase intention, online shopping